ANALISIS PENGAWASAN BERBASIS DATA ANALYTICS DALAM MENINGKATKAN AKUNTABILITAS EVALUASI PENDIDIKAN DI ERA TRANSFORMASI DIGITAL MTS. AL FALAH PUTRI WULUHAN - Nazilatun Nuroini; M. Sidiq Purnomo (As-Sulthan Journal of Education, 2026)
This research aims to analyze the effectiveness of implementing a data analytics-based digital dashboard in improving the transparency, accuracy, and responsiveness of education supervision. The research uses a qualitative method with a case study design combined with a systematic review thru the PRISMA framework. Data collection techniques include field observation, in-depth interviews, performance documentation, and a search of reputable national and international articles. Data analysis techniques used a thematic model, referencing Thematic Analysis by Braun and Clarke, employing a systematic coding process to inductively and deductively identify and interpret key patterns in empirical data, resulting in structured, objective, and contextual interpretations. Data validity was tested using source, technique, and theory triangulation to ensure the validity and reliability of the findings. The research results indicate that utilizing data analytics thru digital dashboards can strengthen performance indicator mapping, provide early detection of quality deviations, present objective visualizations of achievements, and predict risks of declining educational quality, while simultaneously addressing classic problems such as delayed reports, low validity of field findings, and weak coordination between educational units. The implementation of a data analytics-based digital dashboard allows for the real-time, objective, and measurable integration of teacher performance data and learning achievement. The positive impacts include increased transparency, accuracy of evaluation, and speed of supervisory decision-making. Obstacles such as digital literacy limitations and data fragmentation are overcome thru indicator standardization, continuous training, and the integration of systems based on institutional policies.